Long-Term Culturing of FreeStyle 293-F Cells Affects Immunoglobulin G Glycome Composition - Fran Lukšić; Anika Mijakovac; Goran Josipović; Vedrana Vičić Bočkor; Jasminka Krištić; Ana Cindrić; Martina Vinicki; Filip Rokić; Oliver Vugrek; Gordan Lauc; Vlatka Zoldoš (Biomolecules, 2023)
Glycosylation of IgG regulates the effector function of this antibody in the immune response. Glycosylated IgG is a potent therapeutic used for both research and clinical purposes. While there is ample research on how different cell culture conditions affect IgG glycosylation, the data are missing on the stability of IgG glycome during long cell passaging, i.e., cell “aging”. To test this, we performed three independent time course experiments in FreeStyle 293-F cells, which secrete IgG with a human-like glycosylation pattern and are frequently used to generate defined IgG glycoforms. During long-term cell culturing, IgG glycome stayed fairly stable except for galactosylation, which appeared extremely variable. Cell transcriptome analysis revealed no correlation in galactosyltransferase B4GALT1 expression with galactosylation change, but with expression of EEF1A1 and SLC38A10, genes previously associated with IgG galactosylation through GWAS. The FreeStyle 293-F cell-based system for IgG production is a good model for studies of mechanisms underlying IgG glycosylation, but results from the present study point to the utmost importance of the need to control IgG galactosylation in both in vitro and in vivo systems. This is especially important for improving the production of precisely glycosylated IgG for therapeutic purposes, since IgG galactosylation affects the inflammatory potential of IgG.